Characteristics Of Fables And Their Symbols In Eastern And Western Literature (Texas Journal of Philology, Culture and History, 2024)
Symbolism serves as a foundation in literature and offers a subtle lens through which to explore the complexities of life. In this study, the multifaceted role of symbolism in literary works is studied, and special attention is paid to its manifestation in Uzbek literature. Based on the opinions of scientists such as Dilmurod Kuronov, M. Yoldoshev, L. Reznikov, the definition and interpretation of the symbol is deeply studied in the research, and its moral, social and psychological aspects are studied through a comprehensive analysis, the study reveals the widespread use of symbols in various literary genres, illuminating its evolution from ancient folklore to modern expressions